ECOLOGICAL CONSCIOUSNESS IN MARGARET ATWOOD’S NOVEL THE TESTAMENTS: AN ECO-CRITICAL PERSPECTIVE (Contemporary Journal of Social Science Review, 2025)
This study examines Margaret Atwood’s The Testaments using an intertextual analysis, through the lens of ecocriticism, drawing upon the theoretical framework established by Lawrence Buell. The research explores the novel’s engagement with ecological imagination and ecological consciousness, highlighting how Atwood critiques humanity’s exploitative relationship with nature and advocates for sustainable living. The narrative emphasizes the interconnectedness of all living beings, illustrating the profound consequences of environmental degradation resulting from human actions. Atwood underscores the urgency of ecological responsibility, portraying a world where the destruction of natural resources jeopardizes human survival. By weaving ecological themes into the novel’s dystopian setting, she challenges readers to rethink their environmental ethics.This study employs a qualitative research methodology, utilizing textual analysis to examine Atwood’s depiction of ecological awareness and its implications within the narrative. The primary data comprises textual evidence from The Testaments, while secondary sources include scholarly journals, academic articles, theses, and books that provide critical perspectives on Atwood’s ecological themes. Through this analysis, the research aims to contribute to the discourse on ecocriticism in contemporary literature, demonstrating how Atwood’s work reflects and responds to pressing environmental concerns.